Leadership Management Of The Chairman Foundation Coordinating Education Unit Management - Rasid, Rasid; Nasir, Nasir (JURNAL INOVASI DAN MANAJEMEN PENDIDIKAN, 2023)
Problem: The governance of the education unit under the auspices of the foundation is not coordinated measurably in terms of milestones. Purpose: This paper provides direction for the leadership management strategy of the foundation’s chairman in coordinating the management of educational units. Methods: Collection of data and information using observation, direct interviews, the Delpy method, documentation, and physical artifacts. Inductive, process, and goal-oriented Result: the head of the foundation carries out a transformative leadership management strategy coordinating with the management strategy, and coordinating with the educational unit.  The pattern of transformative leadership as a strategy for adapting a harmonious and productive democratic leadership model in mobilizing school principals and teachers to the demands of changes in the management information and technology-based education units, as well as student-oriented leadership strategy that emphasizes the quality of management of educational units under the foundation’s internal supervision, governance of quality-oriented foundations in educational units, developing the quality of teaching and educational staff resources, developing facilities and infrastructure, involving parent of students and benchmarking in educational unit at the same level.